2017
DOI: 10.1037/adb0000298
|View full text |Cite
|
Sign up to set email alerts
|

Functional neural changes following behavioral therapies and disulfiram for cocaine dependence.

Abstract: A growing literature exists on neural correlates of treatment outcome. However, different types - or components of - treatment have distinct theorized mechanisms of action. And, it is not yet known how changes in neural activity across treatment relate to engagement in different treatment components. Participants with cocaine-use disorders in a randomized clinical trial received cognitive behavioral therapy (CBT) plus, in a 2×2 design, contingency management (CM) or no-CM, and disulfiram or placebo. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 76 publications
3
12
0
Order By: Relevance
“…Within a VBDM framework, CBT can be understood as enhancing executive control systems, allowing for more deliberative, less-impulsive decision-making. This is consistent with data showing that CBT-based strategies engage executive control systems (Kober, Mende-Siedlecki, et al, 2010) and that CBT leads to lasting changes in these systems (DeVito et al, 2012, 2017). Additionally, recent evidence suggests that mindfulness-based treatments reduce drug-use (Bowen et al, 2009, 2014); they may do so by reducing the likelihood of maintaining a craving state after seeing drug cues, which reduces substance use behavior (e.g., Elwafi, Witkiewitz, Mallik, Thornhill, & Brewer, 2013; Kober, Brewer, Height, & Sinha, 2017).…”
Section: Summary and Path Forwardsupporting
confidence: 91%
“…Within a VBDM framework, CBT can be understood as enhancing executive control systems, allowing for more deliberative, less-impulsive decision-making. This is consistent with data showing that CBT-based strategies engage executive control systems (Kober, Mende-Siedlecki, et al, 2010) and that CBT leads to lasting changes in these systems (DeVito et al, 2012, 2017). Additionally, recent evidence suggests that mindfulness-based treatments reduce drug-use (Bowen et al, 2009, 2014); they may do so by reducing the likelihood of maintaining a craving state after seeing drug cues, which reduces substance use behavior (e.g., Elwafi, Witkiewitz, Mallik, Thornhill, & Brewer, 2013; Kober, Brewer, Height, & Sinha, 2017).…”
Section: Summary and Path Forwardsupporting
confidence: 91%
“…Several studies have implicated the involvement of the IPL during the treatment of addictive disorders. The cocaine dependent individuals under cognitive-behavioral treatment showed a lower activity in the IPL for task-related neural activity(DeVito et al, 2017). Our recent study also found that the HD individuals under protracted abstinence showed lower activity of IPL when exposed to drug related cues in comparison with the HD individuals under MMT(Wei et al, 2020).…”
mentioning
confidence: 50%
“…Previous studies suggest a positive effect of physical activity on cognitive control, through increased neural efficiency (Erickson, Hillman, & Kramer, 2015 ) in the prefrontal cortex and ACC (Voss et al, 2011 ). Furthermore, a reduction in ACC activity is related to better treatment engagement (Devito et al, 2017 ). It is thus possible that interventions targeting ACC activity, for example through physical activity, could potentially increase neural efficiency (thus reducing activity) in cognitive control-related regions, and subsequently improve cognitive control.…”
Section: Discussionmentioning
confidence: 99%